Diagnostic Value of Left Ventricular Early Inflow-Outflow Index in Determining Severity of Mitral Regurgitation - Vera Yulia; Mefri Yanni; Didik Hariyanto (The Indonesian Heart Association, 2017)
Background: Determining severity of mitral regurgitation (MR) is very important, asit is related with prognosis and management of the disease. Currently, there is no goldstandard exists for quantification of MR severity using echocardiography. AmericanSociety of Echocardiography (ASE) guidelines recommend several parameters basedon integrative criteria using color and spectral Doppler and anatomic measurement.Left Ventricular Early Inflow Outflow Index (LVEIO Index) was proposed as one parameterto assess the severity of MR by omitting geometric error from regurgitantvolume method. Thus, LVEIO index offers a simple, easy and accurate measurementin determining severity of MR.Methods: This study was a diagnostic test research with cross-sectional design. Thesubjects were all patients with organic mitral regurgitation who underwent echocardiographyexamination to measure severity of MR using the LVEIO index as well asother parameters measurements based on parameters of ASE guidelines. Diagnostictest was used to determine the sensitivity, specificity, positive predictive value, negativepredictive value and accuracy of LVEIO index.Results: Of 49 patients in this study, 23 of them have severe MR and 26 are non-severeMR patients. The proportion of gender between two groups almost similar with an agerange from 56 to 61 years and the most common etiology finding was degenerative MR.Echocardiography examination showed the ejection fraction in severe MR was 63±4.2%and 64±3.9% in non-severe MR. The value of LAVI, MPAP, E-wave, VC, EROA andLVEIO index increased parallel with severity of MR (LAVI; 67±18.2 vs. 40±14.2 ml/m2,MPAP; 28±12.8 vs. 20±12.6 mmHg, E-wave 1.5±0.3 vs. 1±0.2 m/s, VC 0.8±0.3 vs.0.5±0.1 cm, EROA 0.4±0.1 vs 0,2±0,1cm2, LVEIO 9±2,4 vs. 5±1,8). The sensitivity,specificity, and accuracy of LVEIO index for diagnosis of severe MR were 86%, 84%,and 89%, respectively.Conclusion: LVEIO can be proposed as a relatively simple, easy and accurate methodin determining severity of MR.